Removal of oil and grease from the surface water of Malihao River, Victorias City, Negros occidental using talaba (Cassostrea spp.) shell. - Regatalio, Kyle Dymer Lopez
A high concentration of oil and grease was found on the surface water of the five sampling sites located at Malihao River, which exceeded the standard set by DENR-EMB for class C and class B river. From the five sampling sites, Site 3 located at the Magnanod River and a tributary river to the Malihao River, contained the highest concentration of 12 mg L^(-1) of oil and grease. The potential of talaba (Crassostrea spp.) shell column to adsorb oil and grease from river water sample, including effect of contact time, was studied. Results show that adsorption rate initially increased and optimal removal efficiency was reached within 90 minutes contact time. S-curve isotherm was observed which fitted with Freundlich model that can indicate that chemisorptions occurred. The application of talaba shell column for the removal of oil and grease from Malihao River have the efficiency to remove approximately 80-100% of the oil and grease present on the river. This demonstrates that the talaba shell could efficiently remove oil and grease present on the sample river water.